Inflammation and neuronal death in the motor cortex of the wobbler mouse, an ALS animal model. Issue 1 (December 2015) - Dahlke, Carolin; Saberi, Darius; Ott, Bastian; Brand-Saberi, Beate; Schmitt-John, Thomas; Theiss, Carsten
Abstract Background Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disorder of the upper and lower motor neurons, characterized by rapid progressive weakness, muscle atrophy, dysarthria, dysphagia, and dyspnea. Whereas the exact cause of ALS remains uncertain, the wobbler mouse (phenotype WR; genotypewr/wr ) equally develops a progressive degeneration of motor neurons in the spinal cord and motor cortex with striking similarities to sporadic human ALS, suggesting the possibility of a common pathway to cell death. Methods With the aid of immunohistochemistry, confocal laser scanning microscopy, and transmission electron microscopy techniques, we analyze the proliferation behavior of microglial cells and astrocytes. We also investigate possible motor neuron death in the mouse motor cortex at different stages of the wobbler disease, which so far has not received much attention. Results An abnormal density of Iba-1-positive microglial cells expressing pro-inflammatory tumor necrosis factor (TNF) alpha- and glial fibrillary acidic protein (GFAP)-positive activated astroglial cells was detected in the motor cortex region of the WR mouse 40 days postnatal (d.p.n.). Motor neurons in the same area show caspase 3 activation indicating neurodegenerative processes, which may cause progressive paralysis of the WR mice. It could also cause cell degeneration, such as vacuolization, dilation of the ER, and swollen mitochondria at the same time, and support the assumption that inflammation might be an important contributing factor of motor neuron degeneration. This would appear to be confirmed by the fact that there was no conspicuous increase of microglial cells and astrocytes in the motor cortex of control mice at any time. Conclusions Activated microglial cells secrete a variety of pro-inflammatory and neurotoxic factors, such as TNF alpha, which could initiate apoptotic processes in the affected wobbler motor neurons, as reflected by caspase 3 activation, and thus, the neuroinflammatory processes might influence or exacerbate the neurodegeneration. Although it remains to be clarified whether the immune response is primary or secondary and how harmful or beneficial it is in the WR motor neuron disease, anti-inflammatory treatment might be considered.